Answer:
(1, 5) and (5, 13)
Step-by-step explanation:
Given the equations is expressed as;
y= x^2 - 4x +8
y= 2x + 3
Since both equations are y values, we will equate the right hand side of both equations to have;
x^2 - 4x +8 = 2x+3
Equate to zero
x^2 - 4x +8 - 2x - 3 = 0
x^2 - 4x - 2x + 8 - 3 = 0
x^2 - 6x + 5 = 0
Factorize
x^2 - 5x - x + 5 = 0
x(x-5) - 1(x - 5) = 0
(x-1)(x-5) = 0
x - 1 = 0 and x-5 = 0
x = 1 and 5
when x = 1
y = 2x+3
y = 2(2) + 1
y = 4 + 1
y = 5
when x = 5
y = 2(5) + 3
y = 10 + 3
y = 13
Hence the solutions to the system of equations are (1, 5) and (5, 13)